Initial experience with extracorporeal membrane oxygenation following cardiac surgery in children with congenital heart disease - Sharma, Apurb; Pokharel, Jeju Nath; Upreti, Murari Raj; Koirala, Bhagawan; Sharma, Jyotindra; Pradhan, Siddartha; Bhatta, Mahendra (Nepalese Heart Journal, 2014)
Background and Aim: Cardiac extra-corporeal membrane oxygenation is a mechanical life support system initiated in patients with extreme cardiopulmonary failure. Extracorporeal circulation after cardiac surgery supports the heart and lungs recover from the acute injuries of the surgery. Aims of this study were to present our initial experience about complications and outcome with the use of extracorporeal membrane oxygenation following open-heart surgery for congenital cardiac anomalies. Methods: Medical records of all pediatric and neonatal patients requiring extracorporeal life support following cardiac surgery for congenital cardiac anomalies were retrospectively reviewed. Patient and extracorporeal system characteristics were evaluated. Results: Between 2009 and 2012, eight children were treated at our institution with mechanical extracorporeal life support system following open heart surgery. Median age was four months and mean weight was 7.24 kilograms. The indications for initiation of extracorporeal support were difficulty in weaning off cardiopulmonary bypass despite maximal inotropic support, refractory pulmonary oedema immediately after cardiopulmonary bypass and right ventricular dysfunction in postoperative period. Two patients were weaned from the extracorporeal support successfully. Conclusions: Initial results of our extra-corporeal membrane oxygenation programme do not meet the international standards. It can still be a valuable strategy for saving lives after paediatric cardiac surgery. DOI: http://dx.doi.org/10.3126/njh.v11i1.10980   Nepalese Heart Journal 2014;11(1): 39-44